Permanent pacemaker implantation for atrioventricular block secondary to acute pancreatitis in a patient affected by panhypopituitarism - Jacopo Giovacchini; Silvia Menale; Irene Merilli; Valentina Scheggi (The Egyptian Heart Journal)
Abstract Background Hypopituitarism may trigger the development of acute pancreatitis (AP) through multiple mechanisms. AP may alter normal intracardiac conduction leading to an atrioventricular block. Due to the lack of similar cases, the correct timing and indication for pacemaker implantation in such a setting are unknown. Case presentation A 22-year-old woman with a history of sub-total excision of frontal astrocytoma with residual panhypopituitarism in replacement therapy was admitted to the emergency department with AP and peripancreatic necrosis, complicated by hypotension, sinus bradycardia with 2:1 atrioventricular block, and severe acute respiratory distress syndrome deserving intubation and mechanical ventilation. During the in-hospital course, the patient developed a systemic inflammatory response syndrome and acute kidney failure and was treated with intravenous dopamine, diuretics, and liquids. While she gradually recovered, advanced atrioventricular block persisted after the resolution of AP; therefore, a permanent pacemaker was implanted. During the follow-up, appropriate device interventions were detected. Conclusions No other cases of high-grade atrioventricular block in panhypopituitarism-induced AP have been reported in the literature. Our case suggests a pacemaker is necessary if the atrioventricular block does not recover with AP resolution. Further evidence is required to improve the management of rhythm disturbances in hypopituitarism patients who develop AP.